On sequential fractional q-Hahn integrodifference equations - Thongchai Dumrongpokaphan (2020)
© 2020 by the authors. In this paper, we prove existence and uniqueness results for a fractional sequential fractional q-Hahn integrodifference equation with nonlocal mixed fractional q and fractional Hahn integral boundary condition, which is a new idea that studies q and Hahn calculus simultaneously.